verify that: x³+y³+2³-3xyz=1/2(X+y+z)[(x-y)²(y-z)²(z-x)²]
Answers
Answered by
5
Answer:
Prove that,
x³ + y³ + z³ - 3xyz
= 1/2 (x + y + z) [(x - y)² + (y - z)² + (z - x)²]
Proof.
To prove this identity, we need to take help of another identity.
We know that,
x³ + y³ + z³ - 3xyz
= (x + y + z) (x² + y² + z² - xy - yz - zx) ...(i)
Now, we just need to change
(x² + y² + z² - xy - yz - zx)
as the sum of square term.
So, x² + y² + z² - xy - yz - zx
= 1/2 (2x² + 2y² + 2z² - 2xy - 2yz - 2zx)
= 1/2 (x² - 2xy + y² + y² - 2yz + z² + z² - 2zx + x²)
= 1/2 [(x - y)² + (y - z)² + (z - x)²]
From (i), we get
x³ + y³ + z³ - 3xyz
= 1/2 (x +y + z) [(x - y)² + (y - z)² + (z - x)²]
Thus, confirmed.
I hope it helps you
Similar questions
English,
29 days ago
Math,
29 days ago
Math,
29 days ago
India Languages,
1 month ago
History,
9 months ago